Retinal Microcirculation in Type 1 Diabetic Patients With and Without Peripheral Sensory Neuropathy - Forst, Thomas; Weber, Matthias M.; Mitry, Michael; Müller, Lena; Forst, Senait; Tanis, Mukkadar; Pfützner, Andreas; Michelson, Georg (Journal of diabetes science and technology, 2014)
In patients with diabetes mellitus (DM), early retinal microvascular alterations can be observed even before the clinical diagnosis of diabetic retinopathy. This study aimed to investigate morphological and functional changes in retinal microvascular blood flow in type 1 diabetic patients with and without peripheral neuropathy (PNP) as compared to nondiabetic controls. Retinal microvascular blood flow (RBF) was assessed using scanning laser Doppler flowmetry (Heidelberg Retina Flowmeter, Heidelberg Engineering, Germany) before and after stimulation with flicker light. PNP was assessed using the neuropathy disability score (NDS) and by the evaluation of the vibration perception threshold (VPT). A total of 41 subjects were recruited for study participation and were stratified to 3 different groups according to their metabolic and neurological status: 14 nondiabetic subjects without PNP, 14 diabetic patients without PNP, and 13 diabetic patients with PNP. All subjects were free from diabetic retinopathy as assessed by fundoscopy. In diabetic patients with PNP, baseline and stimulated RBF was higher compared with diabetic patients without PNP and the nondiabetic control group. No difference with regard to RBF could be observed between the nondiabetic control subjects and patients with type 1 DM without PNP. No difference in the arterial WLR could be observed between the 3 groups. A linear correlation was found for VPT and RBF (r = .38, P < .001) and for NDS and RBF (r = .44, P < .0001). In our study population of patients with type 1 diabetes, PNP was associated with functional but not morphological changes in RBF.
EVALuna2:21192